2012
DOI: 10.1016/j.chiabu.2011.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Number of childhood abuse perpetrators and the occurrence of depressive episodes in adulthood

Abstract: Objective Although past research has documented a link between adverse childhood experiences – particularly childhood emotional (CEA), physical (CPA), and sexual abuse (CSA) – and depression, relatively few studies have examined the unique impact of each of these highly co-occurring abuse types. Moreover, relatively little is known about the specific aspects of abuse experiences that increase risk for depression (e.g., number of perpetrators). The current study provides a conservative test of the association b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 79 publications
3
23
0
1
Order By: Relevance
“…Afifi et al (2008) found that the estimated attributable fractions for psychiatric disorders related to having experienced any ACE (childhood sexual or physical abuse, domestic violence) ranged from 22% to 32% among women and 20% to 24% among men. A particularly strong link has been identified between childhood physical, sexual abuse and neglect and the mood and anxiety disorders (Heim et al, 2008(Heim et al, , 2010Liu et al, 2012;Sachs-Ericsson et al, 2010). For example, researchers found that people who were verbally abused had 1.6 times as many symptoms of depression and anxiety as those who had not been verbally abused and were twice as likely to have suffered a mood or anxiety disorder over their lifetime (Sachs-Ericsson, Verona, Joiner, & Preacher, 2006).…”
Section: Gene-environmentmentioning
confidence: 96%
See 3 more Smart Citations
“…Afifi et al (2008) found that the estimated attributable fractions for psychiatric disorders related to having experienced any ACE (childhood sexual or physical abuse, domestic violence) ranged from 22% to 32% among women and 20% to 24% among men. A particularly strong link has been identified between childhood physical, sexual abuse and neglect and the mood and anxiety disorders (Heim et al, 2008(Heim et al, , 2010Liu et al, 2012;Sachs-Ericsson et al, 2010). For example, researchers found that people who were verbally abused had 1.6 times as many symptoms of depression and anxiety as those who had not been verbally abused and were twice as likely to have suffered a mood or anxiety disorder over their lifetime (Sachs-Ericsson, Verona, Joiner, & Preacher, 2006).…”
Section: Gene-environmentmentioning
confidence: 96%
“…Aspects of the sexual abuse À such as age when sexual abuse first started, frequency, severity and characteristics of the perpetrator, and number of perpetrators À may have differential impact on its effects (Charles, 2010;Liu et al, 2012;Steel, Sanna, Hammond, Whipple, & Cross, 2004). Additionally, the clustering of co-occurring ACE may differentially influence the type of negative life outcomes (Barel, Van, Sagi-Schwartz, & Bakermans-Kranenburg, 2010;Harford, Yi, & Grant, 2014;P.…”
Section: Characteristics Of Ace and Late-life Suicidementioning
confidence: 97%
See 2 more Smart Citations
“…Sexual abuse experiences in childhood confer high risk for developing clinical depression and possible mechanisms by which they play their deleterious effect [81]. Studies point out that a history of childhood sexual abuse is associated with increased risk of major depressive disorder associated with suicidal thoughts and behavior, including suicidal thoughts, persistent suicidal thoughts, suicide plan and at-tempt.…”
Section: Family and Hereditary Factorsmentioning
confidence: 99%